2016
DOI: 10.1177/1049732316651252
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Management Practices as Mechanisms for Re-Establishing Normality in Cancer Survivors

Abstract: This article explores the relationship between cancer survivors' use of self-management practices and their search for normality. Using Frank's illness narratives and other theoretical literature on normality in chronic illness, it draws on findings from a qualitative study to explore different ways cancer survivors use self-management practices to re-establish normality in their lives post-cancer. The findings suggest that "normality" represents different things to cancer survivors. We suggest that normality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 52 publications
3
32
2
Order By: Relevance
“…Participants expressed a desire to take responsibility for their own health needs through self‐care measures, which according to Henshall, Greenfield, and Gale () can support quality of life and well‐being. Some patients may be more motivated to self‐care than others, therefore professional support should be available to help individuals decide and set their own priorities for care (Kidd, Kearney, O'Carroll, & Hubbard, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants expressed a desire to take responsibility for their own health needs through self‐care measures, which according to Henshall, Greenfield, and Gale () can support quality of life and well‐being. Some patients may be more motivated to self‐care than others, therefore professional support should be available to help individuals decide and set their own priorities for care (Kidd, Kearney, O'Carroll, & Hubbard, ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants expressed a desire to take responsibility for their own health needs through self-care measures, which according to Henshall, Greenfield, and Gale (2017) can support quality of life and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…We have conceptualised this psychological adjustment and adaptation as a 'sense of normality'. We have used this term for two reasons: firstly, the patients and parents we spoke to often referred to this component of their experience in reflecting on the overarching impact of the burn injury and treatments using the terms 'normal' or 'normality' and secondly, 'normality' has been used as a conceptual tool to understand the patient experience of other health conditions, particularly chronic conditions, and the adaptations that patients undergo in order to accommodate the condition and its impact on life [27][28][29][30] At present there is a limited range of burn-specific PROs available and only one that is scar-specific (BBSIP). Only two of these measures were developed using qualitative data collected from patients (BBSIP, BSPAS) and the BSPAS is focused exclusively on pain and anxiety related to pain.…”
Section: Treatment Burdenmentioning
confidence: 99%
“…Our findings revealed that some participants could perform physical activities and feel normal. This aspect is interpreted as resuming physical “self.” However, normality is not a static concept that largely depends on the life biography and experience of an individual . In male‐dominated Chinese culture, the existence of “self” for a Chinese woman is often associated with family values; for example, women are traditionally assumed to compromise their own needs, including those of sexual nature, for the sake of their husbands .…”
Section: Discussionmentioning
confidence: 99%
“…However, normality is not a static concept that largely depends on the life biography and experience of an individual. 33 In male-dominated Chinese culture, the existence of "self" for a Chinese woman is often associated with family values; for example, women are traditionally assumed to compromise their own needs, including those of sexual nature, for the sake of their husbands. 34 However, the participants in our study were unwilling to achieve the sexual and social nature of "self" to conform to Chinese societal norms and expectations because of their fears that physical, mental, and sexual overexertion may induce recurrence.…”
Section: Managing Role and Relationshipsmentioning
confidence: 99%